Tip-Over Stability Analysis of a Pelvic Support Walking Robot. (7th February 2020) - Han, Yawei; Guo, Shuai; Zhang, Leigang; Xi, Fengfeng (Jeff); Lu, Weiwei
Abstract : Discussed in this paper is the tip-over stability analysis of a pelvic support walking robot. To improve the activities of daily living (ADL) in hemiplegic patients, a pelvic support walking robot is proposed to help patients facilitating their rehabilitation. During the gait training with the robot, the abnormal man-machine interaction forces may lead to the tip-over of the robot, which is not beneficial to the rehabilitation process. A new method is proposed to predict the possibility of tipping over and evaluate the stability of the robot based on statics model, dynamics model, and zero-moment point (ZMP) theory. Through the interaction forces and moments analysis with static case, the safe point (ZMP) is studied, and the influence factors of force/moment are analyzed by dynamics case. An optimization algorithm based on the genetic algorithm (GA) is proposed to reduce the risk of tipping over. The simulation results show that the optimization algorithm can keep the robot from tipping over when the interaction forces exceed the safety threshold.